THEORETICAL FOUNDATIONS OF THE USE OF PERSON-ORIENTED MODELS IN THE HIGHER EDUCATION SYSTEM (American Journal of Pedagogical and Educational Research, 2024)
To improve the methodology of using individual-oriented logical models in the higher education system and to increase the logical reasoning abilities of students, that is, future teachers, to develop the ability to think as an independent person, as well as the rules of the law of logic have been developed.